Facing loss: pedagogy of death. Issue 8 (3rd August 2019) - Affifi, Ramsey; Christie, Beth
Abstract: Loss, impermanence, and death are facts of life difficult to face squarely. Our own mortality and that of loved ones feels painful and threatening, the mortality of the biosphere unthinkable. Consequently, we do our best to dodge these thoughts, and the current globalizing culture supports and colludes in our evasiveness. Even environmental educators tend to foreground 'sustainability' whilst sidelining the reality of decline, decay, and loss. And yet, human life and ecological health require experiencing 'unsustainability' too, and a pedagogy for life requires a pedagogy of death. In this paper we explore experiences of loss and dying in both human relationships and the natural world through four different types of death affording situations, the cemetery, caring-unto-death, sudden death, and personal mortality. We trace the confluence of death in nature and human life, and consider some pedagogical affordance within and between these experiences as an invitation to foster an honest relationship with the mortality of self, others, and nature. We end by suggesting art as an ally in this reconnaissance, which can scaffold teaching and learning and support us to courageously accept both the beauty and the ugliness that death delivers to life.